Geomorphologic and paleoclimatic evidence of Holocene glaciation on Mount Olympus, Greece. (May 2016) - Styllas, Michael Nikolaos; Schimmelpfennig, Irene; Ghilardi, Matthieu; Benedetti, Lucilla
This study investigates the possibility of Holocene glaciation on Mount Olympus (Greece) with a respective local temperature–precipitation equilibrium line altitude (TP-ELA) at c . 2200 m a.s.l., based on geomorphologic and paleoclimatic evidence. At present, the local TP-ELA is situated above the mountain's summit ( c . 2918 m a.s.l.), but permanent snowfields and ice bodies survive within Megala Kazania cirque between c . 2400 and c . 2300 m a.s.l., because of the cirque's maritime setting that results from its close proximity ( c . 18 km) to the Aegean Sea and of the local topographical controls. The snow and ice bodies occupied a considerably larger area and attained a stabilization phase between AD 1960 and 1980, also manifested from aerial photographs, a period characterized by increased winter precipitation ( P w ) with subsequent TP-ELA depression to c . 2410 m a.s.l. Mid- to late-20th-century P w and TP-ELA variations exhibit negative correlations with the winter North Atlantic Oscillation index (NAOw ) at annual and multidecadal (30 years) timescales. Late Holocene (AD 1680–1860) reconstructed summer mean temperatures were lower by Ts  < 1.1°C in relation to the reference period between AD 1960 and 1980 and were also superimposed to negative NAOw phases, thus bracketing this time interval as a favorable one to glacial formation and/or advance. Millennial-scale annual precipitation reconstructions at the hypothesized TP-ELA ( c . 2200 m a.s.l.) point the period between 8 and 4 kyr BP as another glacier-friendly candidate. The mid-Holocene rather simplistic sequence of potential glacial advance phase was disturbed by short-lived cold climatic deteriorations, well-documented over the northern Aegean region that may partly explain the multicrested shape of the highest ( c . 2200 m a.s.l.) morainic complex of Megala Kazania cirque.